PREVENTIVE AND CURATIVE ASPECTS OF AYURVEDA IN LIFESTYLE DISORDERS - Soniya, *Chaudhary; Pramod, Mishra; Brahmanand, Sharma; Anamika, Soni (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda has two objects: preservation of the health in the healthy and treatment of disorders in the diseased. The multidimensional role of Ayurveda is clear from the title. In present Era, over stress and bad food habits or bad Life style reduces individual happiness and predispose to many disease e.g. dyslipidemia, obesity, cardio vascular disease, diabetes mellitus, hypertension and other clinical conditions. Ayurveda system is for complete well being of an individual. With the changing demand and awareness among people these days, the role of ancient health care systems like Ayurveda is an emerging reality. Shodhana, Shamana & Rasayana therapy along with compliances of Dinacharya, Ritucharya as mentioned In classical Ayurveda texts etc play an important role in promoting the health and prolonging the Life span by establishing homeostasis between Dosha, Dhatu & Mala. It helps to keep diseases free at bay. Ayurveda System of medicine is holistic and free from side effects. Preventive aspect of this system are shown in various dos and don'ts in Dinacharya, Ritucharya, Sadvirtta, Rasayana and Sanshodhana therapy etc. The curative aspect and various drug formulations or regimens has been given described specially in description of the management of various diseases. The role of the Ayurveda in prevention and cure of life style disorders will be explained in full paper.